2016
DOI: 10.1111/jphp.12502
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, in-vitro and in-vivo characterisation of CoQ10 microparticles: electrospraying-enhanced bioavailability

Abstract: Based on the findings in this study, electrospraying is a highly prospective technology to produce functional nano- and micro-structures as delivery vehicles for drugs with poor oral bioavailability due to rate-limiting solubility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Generally, topical antioxidant nanoparticle formulations can effectively reduce the particle size and change the form from crystalline to amorphous for ingredients showing poor water solubility [ 24 ] such as quercetin [ 25 ], resveratrol [ 26 ], lutein [ 27 ], and coenzyme Q10 [ 28 ], increasing their dissolution, skin penetration, and bioavailability. Our preliminary test of this study used PVPK30 or HPBCD as an excipient independently to prepare the ACM nanoparticle.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, topical antioxidant nanoparticle formulations can effectively reduce the particle size and change the form from crystalline to amorphous for ingredients showing poor water solubility [ 24 ] such as quercetin [ 25 ], resveratrol [ 26 ], lutein [ 27 ], and coenzyme Q10 [ 28 ], increasing their dissolution, skin penetration, and bioavailability. Our preliminary test of this study used PVPK30 or HPBCD as an excipient independently to prepare the ACM nanoparticle.…”
Section: Discussionmentioning
confidence: 99%
“…As such, our research group remains committed to further investigating an oro-buccal delivered nanoparticle formulation for the enhanced delivery of CoQ 10 to intracellular and mitochondrial targets. In vitro and in vivo studies have recently demonstrated that electro-spraying microparticles may comprise a possible future technology for improving the bioavailability of compounds such as CoQ 10 [26].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies explored the possibility of using electrospraying to encapsulate enzymes. Fung et al (2016) electrosprayed coenzyme Q10 in copovidone (Kollidon® VA64) using acetone as the solvent. Both in vitro and in vivo evaluation showed enhanced bioavailability of the electrosprayed microparticles.…”
Section: Bioactive Cargos Electrosprayed Inside Carriersmentioning
confidence: 99%